2002
DOI: 10.1186/1297-9686-34-3-371
|View full text |Cite
|
Sign up to set email alerts
|

Results of a whole genome scan targeting QTL for growth and carcass traits in a Piétrain × Large White intercross

Abstract: -We herein report the results of a whole genome scan performed in a Piétrain × Large White intercross counting 525 offspring to map QTL influencing economically important growth and carcass traits. We report experiment-wide significant lod scores (> 4.6) for meatiness and fat deposition on chromosome SSC2, and for average daily gain and carcass length on chromosome SSC7. Additional suggestive lod scores (> 3.3) for fat deposition are reported on chromosomes SSC1, SSC7 and SSC13. A significant dominance deviati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
1
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(51 citation statements)
references
References 20 publications
5
42
1
2
Order By: Relevance
“…Nessa região, Gonçalves et al (2005) detectaram dois QTL significativos para espessura de toucinho, em suínos resultantes do cruzamento entre Meishan, Large White e Landrace. Nas características comprimento de carcaça e espessura de toucinho, os SNP de maior efeito foram encontrados no terço final do cromossomo 7, como observado por Nezer et al (2002) e Sousa et al (2011). Também no cromossomo 4, Silva et al (2011) detectaram QTL significativo na mesma população F 2 , para a característica EBACON, o que está de acordo com o obtido no presente trabalho, no qual observaramse marcadores SNP relevantes nesta região.…”
Section: Resultsunclassified
“…Nessa região, Gonçalves et al (2005) detectaram dois QTL significativos para espessura de toucinho, em suínos resultantes do cruzamento entre Meishan, Large White e Landrace. Nas características comprimento de carcaça e espessura de toucinho, os SNP de maior efeito foram encontrados no terço final do cromossomo 7, como observado por Nezer et al (2002) e Sousa et al (2011). Também no cromossomo 4, Silva et al (2011) detectaram QTL significativo na mesma população F 2 , para a característica EBACON, o que está de acordo com o obtido no presente trabalho, no qual observaramse marcadores SNP relevantes nesta região.…”
Section: Resultsunclassified
“…On the other hand, a highly significant QTL for ADG was mapped to SSC7 (position , 100 cM), close to the region where Houston et al (2005) mapped QTL for average feeding rate, and close to previously reported QTL affecting growth rate (Bidanel and Rothschild, 2002). Some QTL were identified in crosses involving the PI breed in chromosomal regions close to the maximum LRT position in our analysis (Nezer et al, 2002;Edwards et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…When QTL are detected in such populations, they cannot be directly used in selection programmes and additional studies are required to confirm the existence of these QTL in commercial populations. Nevertheless, genome scans are carried out on an increasing -E-mail: marie-pierre.sanchez@jouy.inra.fr number of crosses of commercial populations: Yorkshire 3 Berkshire (Malek et al, 2001a and2001b), Piétrain 3 Large White (Nezer et al, 2002), Iberian 3 Landrace (Varona et al, 2002), Hampshire 3 Landrace (Karlskov-Mortensen et al, 2005) or Duroc 3 Piétrain populations (Liu et al, 2007;Edwards et al, 2008a and2008b) and even on purebred commercial populations (Evans et al, 2003;Vidal et al, 2005;Tribout et al, 2008). All these studies revealed a large number of QTL, suggesting that different alleles are fixed in distinct commercial populations or that QTL are still segregating in purebred populations after many generations of selection.…”
Section: Introductionmentioning
confidence: 99%